Analyzing Speech Acts and Context: Rhetorical Strategies of Trump vs. Biden in 2024 - Sunara, Sunara (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study examines the role of speech acts, contextual influences, and rhetorical strategies in the 2024 presidential debate between Donald Trump and Joe Biden. It identifies a gap in understanding how these elements interact to affect public perception and decision-making during real-time debates. The study aims to analyze how these linguistic features influence public perceptions and the effectiveness of political communication. The study employs qualitative and analytical methods to examine the 2024 presidential debate discourse. It analyzes speech acts (assertives, directives, expressives, and commissives) and rhetorical strategies (ethos, pathos, logos), while considering contextual elements that shape communication. The analysis indicates that 45% of coded utterances are assertive acts (statements and claims), 30% are directive acts (orders or requests), 15% are commissive acts (promises), and 10% are expressive acts (emotions). Trump and Biden use assertive acts to fortify their stances against opponents. Trump often employs aggressive directives, while Biden leans on assertive statements to communicate his vision clearly. Both candidates utilize rhetorical devices to enhance their messages. Effective speech acts and rhetoric shape voter perceptions and influence electoral outcomes. Contextual factors play a significant role in the discourse, with 40% tied to linguistic context, 35% to cultural context, and 25% to situational context. Notably, about 40% of dialogues involve language choices, phrases, and rhetorical devices, underscoring the prominence of linguistic context. Context significantly influences political discourse, and effective communication strategies are essential for influencing voter attitudes in the 2024 presidential debate.